Penggunaan Bahasa Daerah sebagai Mediator dalam Pembelajaran Agama Katolik Bagi Siswa SD YPPK St. Samuel Mokbiran Kabupaten Boven Digoel Provinsi Papua Selatan - Berlinda Setyo Yunarti; Elisabeth Kanyek (JURNAL PASTORAL KATEKETIK, 2025)
This study aims to analyze the use of local language as a mediator in learning Catholic Religion for students of SD YPPK St. Samuel Mokbiran in Boven Digoel Regency, South Papua Province. The background of this research is the limited mastery of Indonesian language by students who are more fluent in Muyu Kawiyet local language. Qualitative research method was used with data collection through observation and interview. The results show that the use of local language in the learning process helps students understand religious materials better, especially the main prayers of Catholicism. However, it also hinders their mastery of Indonesian, which impacts on their overall academic development. This study suggests the increased use of bilingual approaches and the provision of more adequate learning facilities to overcome this problem.